Efikasi Konseling Kelompok Cognitive Behavior Therapy dengan Teknik Self-Instruction untuk Meningkatkan Kepercayaan Diri - Ummi Qudsiyah; Ayu pernama (Kuras Institute, 2022)
The purpose of this study was to determine the level of self-confidence, which is a positive attitude of an individual that enables him/herself to develop positive judgments, using group counseling the Cognitive Behavior Therapy Group Counseling Efficacy approach with Self-Instruction Techniques to Increase Self-Confidence. This study uses a quantitative approach with quasi-experimental research methods. The design used in this study used a pretest and multiple posttest repeated measure experimental design. From the results obtained, it can be said that there was significant interaction between times (pre-test, post-test, and follow-up) in the self-confidence group given self-instruction techniques of (M = 85.71, SE = 4.24). Based on the research that has been done, it can be seen that group counseling with self-instruction techniques is effective in increasing the self-confidence of students who use social media at SMP Negeri 13 Semarang.